Analysis of Water Quality Based On Phytoplankton Abundance And Number of Nutrients - Deffi Ayu Puspito Sari; Rahma Dewi Hutami; Aqil Azizi; Sirin Fairus (Faculty of Agriculture, Merdeka University Surabaya, 2019)
The process of development has effect on the existing water catchment area, currently the normalization of the water area is being carried out. The water body is passed by various kinds of waste; domestic and industrial waste, causing water bodies to contain nutrients. Nutrients are a food source for existing phytoplankton. The amount of nutrients and phytoplankton affects the level of fertility and trophic status of each of these water bodies. Samples were collected from Epicentrum Pond, Lake Sunter, Citra Lake 6, Lake Citra 8, Setu Rawa Badak Jatijajar, and Situ Cilodong. The result shows that are samples classified in the class II water quality category according to PP No. 82/2001. The classification is based on the concentration of pH parameters, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Phosphate and Nitrate. While the classification of aquatic fertility is based on the abundance of phytoplankton. The result shows that Epicentrum Pond, Lake Sunter, Lake Citra 6, Lake Citra 8, and Setu Rawa Badak Jatijajar are included in mesotrophic, while for Situ Cilodong are included in oligotrophic. For the classification of trophic status according to PERMENLH No.28/2009 (based on the parameters of nitrate, phosphate and chlorophyll-a), the Epicentrum Pool is included in the oligotroph to eutroph. Whereas for Lake Sunter, Setu Rawa Badak Jatijajar, and Situ Cilodong are included in oligotrophs to mesotrophs. And for Lake Citra 6 and Danau Citra 8 have trophic status from oligotrophs to hypereutrophs.